Health-related quality of life in hypertensive patients with chronic kidney disease in low and middle-income countries - Wening Wulandari; Neily Zakiyah; Cherry Rahayu; Irma M. Puspitasari; Auliya A. Suwantika (BMC Nephrology)
Abstract Hypertension and chronic kidney disease (CKD) are interconnected conditions that can significantly affect a person’s health-related quality of life (HRQoL). In low- and middle-income countries (LMICs), this disease burden is heightened due to limited health resources and socio-economic challenges. Based on the available literature, this narrative review aims to discuss the HRQoL of hypertensive patients with CKD in LMICs by identifying the current challenges and providing insights into the strategic potential to improve patient’s quality of life. This review reveals that the hypertensive population with CKD has a much lower HRQoL than the general population. Various factors, including physical limitations, comorbidities, psychological barriers, logistical challenges, and social support, can influence HRQoL. Limited access to health care, inadequate resources, and a lack of skilled personnel in LMICs further exacerbate these individual challenges. The economic impact of decreased work productivity and increased health costs adds to the disease burden. Improved health access, effective self-management strategies, and social support are needed to improve HRQoL in hypertensive patients with CKD.